2019
DOI: 10.29252/ibj.23.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deuterium-Depleted Water on the Isotope D/H Composition of Liver Tissue and Morphological Development of Rats at Different Periods of Ontogenesis

Abstract: Background: This study aimed to evaluate the reaction of organism of laboratory animals on deuterium-depleted drinking diet. To assess the cell energy metabolism, the effect of a liquid medium with different deuterium contents on isolated liver mitochondria of random bred rats and Wistar rats was studied. Methods: This experimental study on the effect of deuterium-depleted drinking water (DDW) on 16-week-old male Wistar rats lasted for four weeks. Energy metabolism of mitochondria was examined through the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The administration of water with a reduced deuterium content into the drinking diet leads to a change in the 2 H/ 1 H ratio in the body tissues due to the hydrogen isotopes exchange [18], in particular, as shown by the recent study, the antiproliferation effects of DDW are associated with the occurrence of an imbalance in the mitochondria between the production of reactive oxygen species and their neutralization [19]. Some studies have shown an increase in H 2 O 2 production by mitochondria during their pre-incubation in the deuterium depleted media [20,21]. In addition, the mechanisms of DDW influence on biological systems from the point of view of the medical biochemistry are logically explained by a modification in the mitochondria energy balance [22,23].…”
Section: Introductionmentioning
confidence: 95%
“…The administration of water with a reduced deuterium content into the drinking diet leads to a change in the 2 H/ 1 H ratio in the body tissues due to the hydrogen isotopes exchange [18], in particular, as shown by the recent study, the antiproliferation effects of DDW are associated with the occurrence of an imbalance in the mitochondria between the production of reactive oxygen species and their neutralization [19]. Some studies have shown an increase in H 2 O 2 production by mitochondria during their pre-incubation in the deuterium depleted media [20,21]. In addition, the mechanisms of DDW influence on biological systems from the point of view of the medical biochemistry are logically explained by a modification in the mitochondria energy balance [22,23].…”
Section: Introductionmentioning
confidence: 95%